RECYCLING OF COMMERCIAL PIGGERY WASTES IN SEMI-INTENSIVE CARP POLYCULTURE UNDER RAIN-FED POND ENVIRONMENT IN ASSAM: AN ECONOMIC ANALYSIS - BHATTACHARJYA, B K; BARMAN, K; YENGKOKPAM, S; DEBNATH, D; DAS, P; SHARMA, N; PEGU, S R; YADAV, A K; BORAH, S; SARMA, K K; GOGOI, P; KAKATI, A; et al. (Journal of the Inland Fisheries Society of India, 2021)
An experiment was conducted on integrated pig-cum-fish farming in a large rain-fed pond (1.1 ha) in Assam, India. The pond stocked with fingerlings of Gibelion catla (species ratio 25%), Hypophthalmichthys molitrix (15%) Labeo rohita (15%), Barbonymus gonionotus (5%), Ctenopharyngodon idella (10%), Cirrhinus mrigala (20%) and Cyprinus carpio (10%) at stocking density of 6000 no./ha received wastes from 18 piglets reared for 6 months. Specific growth rate and weight gain% was the highest in silver carp (2.24 and 5519%) followed by common carp (1.81, 25.15%), grass carp (1.71, 20.60%), catla (1.64, 18.27%), mrigal(1.57, 15.94%), silver barb (1.28, 9.09%) and lowest in rohu (0.82, 3.36%). Catla contributed highest to total of fish production (30.3%) followed by silver carp (24.2%) and common carp (20.2%). Average individual weight of pigs was 92 kg. The high fish production (3564 kg/ha/6 months), pig production (1656 kg/ 6 months) and B:C ratio (2.38) showed better profitability of pig-cum-fish farming in rainfed pond. Key words: Pig farming, Fish culture, Assam, IMC, Exotic carps, Silver barb.